Mathematical modelling of inclusion motion and entrapment in billet mould with effect of electromagnetic stirring. (21st October 2019) - Yin, Yanbin; Zhang, Jiongming; Dong, Qipeng; Zhou, QingHai
ABSTRACT: In-mould electromagnetic stirring (M-EMS) is a widely used technique during continuously casting (CC). To investigate the M-EMS effect on the inclusion motion and entrapment in a billet CC mould, a coupling mathematical model was developed. The result indicates that the M-EMS changes molten steel flow pattern and transient inclusion distributions in the mould. Inclusions have a tendency to move close to the mould centre under M-EMS. When the M-EMS is off, the distributions of inclusions in the solidified shell is relatively uniform. When the M-EMS is applied, many inclusions are entrapped near the stirrer mid-plane. Furthermore, distances of captured inclusions below the billet surface become larger. Additionally, the M-EMS has a significant effect on the overall removal fraction of inclusions. At last, detection of inclusions in samples obtained from a plant has been performed. A similar tendency can be found between the predicted and experimental results.